Communicating Wastewater Surveillance information in Montana - Hopkins, Beth (My University, 2023)
On March 11, 2020, the World Health Organization declared COVID-19 a pandemic. With this pandemic came many public health challenges, including how to capture accurate, timely data to determine the burden of COVID-19 in communities. In Montana, community members do not always seek medical care, have access to testing, nor report their at-home test results. Wastewater surveillance mitigates this lack of accurate data by collecting and testing for the concentration of SARS-CoV-2 in the wastewater. This process is independent of the healthcare and reporting systems and the data aides in the decision process for public health action. Public health action includes prioritizing the provision of supplies (test kits, personal protective equipment, staff, vaccines, etc.) and to recommend implementation of masking, social distancing, and other strategies to decrease disease transmission. Wastewater surveillance trends at two sites in Montana, Helena and East Helena, were compared to reported COVID- 19 cases over a three-year period to determine if wastewater trends forecast reported COVID-19 cases. A forecast of COVID-19 cases could allow for more effective public health action to reduce disease transmission. Communication to the public is a significant part of the wastewater surveillance program. With a variety of participating stakeholders, different communications strategies were identified and implemented to relay pertinent wastewater surveillance information. During this APE/ILE, a Montana- based public facing web page and social media posts were created to communicate these data. A flow chart of Montana’s wastewater surveillance program and associated stakeholders was also created to further examine the steps and communication that are needed to have an effective wastewater surveillance program.
Keywords: Wastewater; surveillance; communication; public health; trends; SARS- CoV-2; COVID-19; Montana